74. Empiric Antibiotic Therapy and Community-onset Bacterial Co-infection in Patients Hospitalized with COVID-19: A Multi-hospital Cohort Study. (31st December 2020) - Vaughn, Valerie; Gandhi, Tejal N; Petty, Lindsay A; Patel, Payal K; Prescott, Hallie; Malani, Anurag N; Ratz, David; McLaughlin, Elizabeth; Chopra, Vineet; Flanders, Scott A
Abstract: Background: Antibiotic therapy has no known benefit against COVID-19, but is often initiated out of concern for concomitant bacterial infection. We sought to determine how common early empiric antibiotic therapy and community-onset bacterial co-infections are in hospitalized patients with COVID-19. Methods: In this multi-center cohort study of hospitalized patients with COVID-19 discharged from 32 Michigan hospitals during the COVID-19 Michigan surge, we describe the use of early empiric antibiotic therapy (within the first two days) and prevalence of community-onset bacterial co-infection. Additionally, we assessed patient and hospital predictors of early empiric antibiotic using poison generalized estimating equation models. Results: Between 3/10/2020 and 5/10/2020, data were collected on 951 COVID-19 PCR positive patients. Patient characteristics are described in Table 1 . Nearly two thirds (62.4%, 593/951) of COVID-19 positive patients were prescribed early empiric antibiotic therapy, most of which (66.2%, 393/593) was directed at community-acquired pathogens. Across hospitals, the proportion of COVID-19 patients prescribed early empiric antibiotics varied from 40% to 90% (Figure 1 ). On multivariable analysis, patients were more likely to receive early empiric antibiotic therapy if they were older (adjusted rate ratio [ARR]: 1.01 [1.00–1.01] per year), required respiratory support (e.g., low flow oxygen, ARR: 1.16 [1.04–1.29]), had signs of a bacterial infection (e.g., lobar infiltrate, ARR: 1.17 [1.02–1.34]), or were admitted to a for-profit hospital (ARR: 1.27 [1.11–1.45]); patients admitted later were less likely to receive empiric antibiotics (April vs. March, ARR: 0.72 [0.62–0.84], Table 2 ). Community-onset bacterial co-infections were identified in 4.5% (43/951) of COVID-19 positive patients (2.4% [23/951] positive blood culture; 1.9% [18/951] positive respiratory culture). Conclusion: Despite low prevalence of community-onset bacterial co-infections, patients hospitalized with COVID-19 often received early empiric antibiotic therapy. Given the potential harms from unnecessary antibiotic use, including additional personal protective equipment to administer antibiotics, judicious antibiotic use is key in hospitalized patients with COVID-19. Disclosures: Tejal N. Gandhi, MD, Blue Cross Blue Shield of Michigan (Grant/Research Support) Scott A. Flanders, MD, Agency for Healthcare Research and Quality (Research Grant or Support)Blue Cross Blue Shield of Michigan (Research Grant or Support)